Capital market and the transmission channel of the monetary policy: empirical evidence on the money view - Caroline Geetha (The International Business & Economics Research Journal (IBER), 2010)
The aim of this study is to find the relationship between the monetary transmission channels with the stock prices. The study utilizes the monthly data from 1990 to 2001 obtained from the Kuala Lumpur Stock Exchange Report and the monthly bulletin of the Central Bank of Malaysia. The result revealed that all the variables are non-stationary at the level form and stationery at the first difference. The Johansen Cointegration revealed that a long-run relationship does exist for the unanticipated changes in money supply, unlike the anticipated changes in money supply that only established a short-run relationship with stock prices. This is due to the level of monetization that is unable to eliminate the excess in the money market in the long run.